High muscular fitness has a powerful protective cardiometabolic effect in adults: influence of weight status (2016)
Background: Low levels of muscular fitness (MF) are recognized as an important marker of nutritional status and a predictor of metabolic complications, cardiovascular disease and death, however, the relationship between MF, body mass index (BMI) and the subsequent cardiometabolic protective effects has been less studied among Latin American populations. This study identified an association between MF and the cardiometabolic risk score index (CMRSI) and the lipid-metabolic cardiovascular risk index (LMCRI) in a wide sample of university students grouped according to their BMI. Methods: Six thousand ninety five healthy males (29.6 ± 11.7 year-old) participated in the study. Absolute strength was measured using a T.K.K. analogue dynamometer (handgrip), and the participant’s strength was then calculated relative to their body mass (MF/BM). The LMCRI was derived from the levels of triglycerides, low-density lipoprotein cholesterol (LDL-c), high-density lipoprotein cholesterol (HDL-c), and glucose levels in a blood sample. The CMRSI was calculated by summing the standardized residuals (z-score) for waist circumference, total cholesterol, LDL-c, triglycerides, HDL-c, and median blood pressure. Subjects were divided into six subgroups according to BMI (normal vs. overweight/obese) and MF/BM tertiles (unfit, average, fit). Results: The group of participants with low and moderate levels of MF/BM showed higher CMRSI values independent of BMI (P 0.001). The group with normal BMI and high MF/BM had the highest levels of cardiometabolic protection. All overweight/obese BMI groups had significantly higher LMCRI values independent of the level of MF/BM (P 0.001). Conclusions: Participants with high MF/BM showed reduced cardiometabolic risk, which increased significantly when they were within normal parameters.